Uso de diuréticos tiazídicos como factor protector de fractura de radio distal en pacientes adultos mayores del Hospital Belén de Trujillo - Collave Carranza, Segundo Ernesto (2020)
Distal radius fractures are the most frequent in relation to other fractures, which is associated with osteoporosis in people over 60 years of age, which is why it is considered a current public health problem. The purpose of our study is to demonstrate whether the use of thiazide drugs is a protective factor for strengthening bone quality and therefore reducing the presentation of distal radius fractures in older adults, since there is diverse literature that supports this association. Type of research: analytical, observational, case-control, retrospective. Objective: To determine if the use of thiazide diuretics is a protective factor for distal radius fracture in elderly patients at Belen Hospital of Trujillo. Location and Institution where the academic work will be carried out: Belen Hospital of Trujillo - Trujillo - La Libertad. Duration: 6 months from December 1, 2019 to May 30, 2020. Funding: Author's own resources. Materials and Methods: Our study population will be adult patients over 60 years of age treated at the Belen Hospital of Trujillo Traumatology Service for distal radius fractures during the period 2017 - 2019 that meet the selection criteria, by capturing the medical records of the patients in each study group, by simple random sampling, according to the results of the findings of the distal radiograph. The pertinent data corresponding to the findings recorded in the clinical history will be collected to define the consumption of thiazide drugs in patients over 60 years of age; likewise, information corresponding to the intervening variables considered in the research will be collected; which will be incorporated into the data collection sheet (Annex 1). Data analysis: They will be processed using the IBM V SPSS 23 statistical package. In the statistical analysis, the Chi Square test (X2) will be used for qualitative variables; the associations will be considered significant if the possibility of making a mistake is less than 5% (p <0.05). The odds ratio (OR) offered by the use of thiazides in relation to the risk of distal radius fracture will be obtained. The 95% confidence interval of the corresponding statistician will be calculated.